Tinjauan Histopatologik Penyakit Trofoblastik Gestasional di Sumatera Utara pada Tahun 2010-2013 - . Soekimin (Majalah Patologi Indonesia, 2014)
Background Gestational trophoblastic disease (GTD) was a heterogeneous group of diseases associated with pregnancy, including partial mole, complete mole, invasive mole, choriocarcinoma and placental site trophoblastic tumor. The incidence of GTD varies in different parts of the world. The malignant potential of this disease was higher in South East Asia in comparison to western countries. The aim of the study was to view the variety of histopathological feature of GTD in Medan. Methods This study was a descriptive study, all cases of the gestational trophoblastic cases from Januari 2010 to June 2013 available at the Department of Anatomical Pathology Faculty of Medicine, University of North Sumatera were included in this study. Results Gestational Trophoblastic Disease mostly found in women in their reproductive period. Most patients were over than 40 years (26 cases, 50%), followed by ages between 20 and 40 years (25 cases, 48.08%) and an age less than 20 years (1 case, 1.92%).Histologic classification of all GTD cases revealed most of the cases were partial hydatidiform mole (35 cases, 67.31%), complete hydatidiform mole (8 cases, 15.38%), invasive mole (3 cases, 5.77%), high risk mole (4 cases, 7.69%); and placental site trophoblastic tumors (2 cases, 3.85%) Conclusion Hydatidiform mole was the most type of gestational trophoblastic disease. In this study the partial mole was more frequent than complete mole. Key words : complete mole, gestational trophoblastic disease, hydatidiform mole, partial mole.